2005
DOI: 10.1016/j.stam.2005.06.018
|View full text |Cite
|
Sign up to set email alerts
|

The field emission properties of high aspect ratio diamond nanocone arrays fabricated by focused ion beam milling

Abstract: High aspect ratio diamond nanocone arrays are formed on freestanding diamond film by means of focused ion beam (FIB) milling technology and hot-filament chemical vapor deposition (HFCVD) method. The structure and phase purity of an individual diamond nanocone are characterized by scanning electron microscopy (SEM) and micro-Raman spectroscopy. The result indicates that the diamond cones with high aspect ratio and small tip apex radius can be obtained by optimizing the parameters of FIB milling and diamond grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In theoretical case, β can be expressed as h / r , where h is the height of emitter and r is the average radius of the emitter tips [34]. In this paper, the In 2 O 3 nanostructures in Figure 1 are in random alignment so that the height of emitter is difficult to measure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In theoretical case, β can be expressed as h / r , where h is the height of emitter and r is the average radius of the emitter tips [34]. In this paper, the In 2 O 3 nanostructures in Figure 1 are in random alignment so that the height of emitter is difficult to measure.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the field enhancement factor β is a key parameter, which reflects the enhanced electron emission due to the localized electronic states by the geometrical configuration of the emitters. In theoretical case, β can be expressed as h / r , where h is the height of emitter and r is the average radius of the emitter tips [ 34 ]. In this paper, the In 2 O 3 nanostructures in Figure 1 are in random alignment so that the height of emitter is difficult to measure.…”
Section: Resultsmentioning
confidence: 99%
“…In the syntheses of UNCD films, microwave plasma chemical vapor deposition (MPCVD) using Ar-rich/CH 4 growth chemistry was frequently used for achieving the enhancement of species activity and diamond secondary nucleation to form nano-sized grains [10][11][12][13]. Ultrasonication in diamond powder suspended solutions was commonly used for enhancing the formation of diamond nuclei on foreign substrates [7,[13][14][15][16]. However, improving the syntheses and performance of UNCD films for functional applications should develop new technique, process, pretreatment, and even synthesis system that make the fabrication of UNCD films with higher growth rate, higher doping efficiency, smoother surface, and lower cost, besides the way of optimizing the synthesis process from original Ar-rich growth chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond microtips were made previously for example by reactive ion etching of polycrystalline diamond film 10 . This relatively simple method provides polycrystalline diamond emitters in the shape of microcones which demonstrate metallic type of electron emission with linear Fowler-Nordheim (FN) plots 11 . It has been revealed that emission properties in this case are determined by a conducting amorphous (i.e.…”
mentioning
confidence: 99%